Engaging the public in healthcare decision-making: results from a Citizens' Jury on emergency care services. Issue 11 (20th June 2016) - Scuffham, P A; Moretto, N; Krinks, R; Burton, P; Whitty, J A; Wilson, A; Fitzgerald, G; Littlejohns, P; Kendall, E
Abstract : Background: Policies addressing ED crowding have failed to incorporate the public's perspectives; engaging the public in such policies is needed. Objective: This study aimed at determining the public's recommendations related to alternative models of care intended to reduce crowding, optimising access to and provision of emergency care. Methods: A Citizens' Jury was convened in Queensland, Australia, to consider priority setting and resource allocation to address ED crowding. Twenty-two jurors were recruited from the electoral roll, who were interested and available to attend the jury from 15 to 17 June 2012. Juror feedback was collected via a survey immediately following the end of the jury. Results: The jury considered that all patients attending the ED should be assessed with a minority of cases diverted for assistance elsewhere. Jurors strongly supported enabling ambulance staff to treat patients in their homes without transporting them to the ED, and allowing non-medical staff to treat some patients without seeing a doctor. Jurors supported (in principle) patient choice over aspects of their treatment (when, where and type of health professional) with some support for patients paying towards treatment but unanimous opposition for patients paying to be prioritised. Most of the jurors were satisfied with their experience of the Citizens' Jury process, but some jurors perceived the time allocated for deliberations as insufficient. Conclusions: These findings suggest that the general public may be open to flexible models of emergency care. The jury provided clear recommendations for direct public input to guide health policy to tackle ED crowding.